2007
DOI: 10.4315/0362-028x-70.10.2306
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Listeria monocytogenes on Sliced Ham and Turkey Products Using Benzoate, Propionate, and Sorbate

Abstract: The objective of this study was to identify concentrations of sorbate, benzoate, and propionate that prevent the growth of Listeria monocytogenes on sliced, cooked, uncured turkey breast and cured ham. Sixteen test formulations plus a control formulation for each product type were manufactured to include potassium sorbate, sodium benzoate, or sodium propionate, used alone and combined (up to 0.3% [wt/wt]), or with sodium lactate-sodium diacetate combinations. Products were inoculated with L. monocytogenes (5 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…0.3 to 0.6 and 0.2 to 1.0 log CFU/g, respectively, after 14 days of storage at 4uC. As another example, Glass et al (16) evaluated the effectiveness of up to 0.3% potassium sorbate, sodium benzoate, and sodium propionate, or combinations thereof, as ingredients in sliced uncured turkey breast and hams and reported that these antimicrobials suppressed outgrowth of L. monocytogenes for up to 84 days at 4uC with negligible effects on sensory attributes. In another study, Glass et al (15) found that inclusion of 0.05% sodium benzoate and 0.05% sodium propionate as ingredients in uncured turkey In prefatory studies, we evaluated several antimicrobials for their effect on cells of L. monocytogenes that were surface inoculated onto slices of pork scrapple.…”
Section: Discussionmentioning
confidence: 96%
“…0.3 to 0.6 and 0.2 to 1.0 log CFU/g, respectively, after 14 days of storage at 4uC. As another example, Glass et al (16) evaluated the effectiveness of up to 0.3% potassium sorbate, sodium benzoate, and sodium propionate, or combinations thereof, as ingredients in sliced uncured turkey breast and hams and reported that these antimicrobials suppressed outgrowth of L. monocytogenes for up to 84 days at 4uC with negligible effects on sensory attributes. In another study, Glass et al (15) found that inclusion of 0.05% sodium benzoate and 0.05% sodium propionate as ingredients in uncured turkey In prefatory studies, we evaluated several antimicrobials for their effect on cells of L. monocytogenes that were surface inoculated onto slices of pork scrapple.…”
Section: Discussionmentioning
confidence: 96%
“…Temperature dependent inhibition of L. monocytogenes was also observed by Glass, McDonnell, Rassel & Zierke (2007) while testing the inhibitory effect of benzoate, propionate, and sorbate in sliced ham and turkey products. Inhibition was less pronounced when formulations were stored at abuse temperatures (7 and 10 C), compared to 4 C.…”
Section: Inhibition Of Listeria Monocytogenes In Meat Patémentioning
confidence: 88%
“…It is involved in a number of functions: 1) it controls the development of some pathogenic species (Duffy, Vanderlinde, & Grau, 1994;Glass, McDonnell, Rassel, & Zierke, 2007;Yetim, Kayacier, Kesmen, & Sagdic, 2006); 2) it develops the typical pink colour of cooked ham (Cornforth & Jayasingh, 2004;Lawrie, 1998); 3) it contributes to flavour formation (Guillard, Goubet, Salles, Le Quéré, & Vendeuvre, 1998); and 4) it exerts an antioxidant action against fats (Gatellier, Lessire, Hermier, Maaroufi, & Renerre, 2003;Han & Yamauchi, 2000). On the other hand, nitrite also plays a substantial role in formation of the carcinogenic N-nitrosamine in meat, especially under the process conditions applied in the meat processing industry (Juncher et al, 2000;Lijinsky, 1999;Ward et al, 2007).…”
Section: Introductionmentioning
confidence: 99%